An integrative discursive pragmatics study of sarcastic humor in Instagram Reels, August–September 2025 - Irene Imelda Gulo; R. Kunjana Rahardi (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2026)
This study aims to describe the pragmatic markers, meanings, and functions of sarcastic humor in Instagram Reels comments on the @laporpak_trans7 account during August–September 2025. Sarcastic humor on social media functions not only as entertainment but also as a medium for socio-political criticism and public responses to policy issues. This research employed a descriptive qualitative approach based on integrative discourse pragmatics. The data consisted of 50 sarcastic utterances collected from comments on five Instagram Reels videos. Data were gathered through observation and note-taking techniques and analyzed using cybertextual contexts. The findings indicate that sarcastic humor is marked by hyperbole, identity-based wordplay, direct satire, evaluative diction, and emoticons that help convey sarcastic intentions in digitalcommunication. The meanings expressed through sarcastic humor include criticism of government policies, public officials’ behavior, the use of state facilities, and policy transparency. Functionally, sarcastic humor serves as a medium for emotional expression, social criticism, symbolic reprimand of those in power, and representation of public opinion. The study concludes that sarcastic humor represents a multimodal form of communication and symbolic social resistance in digital spaces. Its novelty lies in integrating the analysis of pragmatic markers, meanings, and funct ions within cybertextual contexts, providing a more comprehensive understanding of sarcastic humor as socio-political expression in the digital public sphere.